Synthesis and characterization of structural, microstructural and ferroic properties of CoFe2O4 nanoparticles and CoFe2O4:BaTiO3 core-shell nanocomposites. Issue 174 (1st September 2016) - Oliveira, P. N.; Alanis, D.; Bini, R. D.; Silva, D. M.; Dias, G. S.; Santos, I. A.; Cótica, L. F.; Guo, R.; Bhalla, A. S.
ABSTRACT: Cobalt ferrite magnetic nanoparticles (CFO) and CoFe2 O4 :BaTiO3 (CFO:BTO) nanocomposites were synthesized successfully by a polymeric method and by a combination of polymeric and citrate-gel methods, respectively. Nanoparticles with a uniform shape, good size distribution and a core-shell microstructure were observed by transmission electron microscopy images. X-ray diffraction and ATR-FTIR results attested a cubic spinel structure for CFO nanoparticles and composites core, as well as a BTO tetragonal perovskite structure for nanocomposites shell. All samples presented a ferrimagnetic-like behaviour at 300 K, with coercive fields of 325 Oe and 840 Oe and saturation magnetizations of 46.2 and 59.6 emu/g, respectively, for CFO and CFO:BTO (3:2).